Nutritional status of institutionalized elderly - Aung, Khin Thandar; Semsuddin @ Zulkifli, Siti Syazwina (Scholars Academic and Scientific Publisher, 2016)
Malnutrition is a serious problem and become a global issue among elderly, especially who are institutionalized. A good nutritional status will promote elderly’s health as well as reduce mortality and morbidity rate among elderly. In Malaysia, the number of the elderly population is increasing and the need for extensive and current information regarding on this population are also increased. Moreover, under nutrition or protein-energy malnutrition becomes more common among elderly. However, there is little information regarding on the health, nutritional status and their social conditions. Therefore, it is an essential for health care providers to assess nutritional status of the elderly in order to manage this problem. The objective of this study was to examine the level of nutritional status among institutionalized elderly. Stratified random sampling was used and total sample size was 80 elderly from selected nursing homes. The level of nutritional status of elderly was assessed using the Mini Nutritional Assessment form and described as in percentage and frequencies. The majority of institutionalized elderly were at risk of malnutrition (70%), while (25%) of them were malnourished and only (5%) were at normal nutritional status. It is found that there was a relationship between Body Mass Index (BMI) and their nutritional status. Most of the elderly in the institutionalized area (nursing homes) at Kuantan, Pahang was at risk of malnutrition. This assessment will help health care providers in detecting the nutritional problem early and plan for the intervention and promote wellness among elderly.